2023
DOI: 10.3389/feart.2022.1036281
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic model for minimizing pressure loss in the wellbore during drilling by considering the effects of cuttings

Abstract: Because of the existence of cuttings in the flow, the pressure loss in the wellbore can increase significantly. Minimization of the flow pressure loss greatly benefits the drilling process. This work investigates the most important factors to the pressure loss in the wellbore during the hole cleaning process. It is found that, for the solid–liquid, two-phase flow, the fluid flow rate is not always proportional to annular pressure loss as the single-phase flow. The mechanisms behind this effect are studied, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…In studies relating to River Ammer floods in Germany, Rimbu et al [2021] observed the frequency of flood years is relatively high with the solar activity is low and vice versa. Li et al [2023] investigated the time-lagged correlations between solar activity and summer precipitation in the mid-lower reaches of the Yangtze River, China and it was observed that the sunspot number has a negative correlation with precipitation, with a time lag of 11 months.…”
Section: • Excess Rainfall Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies relating to River Ammer floods in Germany, Rimbu et al [2021] observed the frequency of flood years is relatively high with the solar activity is low and vice versa. Li et al [2023] investigated the time-lagged correlations between solar activity and summer precipitation in the mid-lower reaches of the Yangtze River, China and it was observed that the sunspot number has a negative correlation with precipitation, with a time lag of 11 months.…”
Section: • Excess Rainfall Studiesmentioning
confidence: 99%
“…The solar influence on rainfall has been a matter of concern for long and many possible links have been discussed in different works [Li et al, 2023]. The presence of similar periods in the time series of rainfall and the solar activity implied a possible relation between them [Heredia et al, 2019, Nitka & Burnecki, 2019.…”
Section: • Excess Rainfall Studiesmentioning
confidence: 99%